Transition to adult services for young people suffering from life-limiting neurodevelopmental disabilities: A case series. (2nd November 2022) - Cheng, Hon Wai Benjamin; Li, Chak Ho Rever; Yeung, K. Y.; Lee, Tracy; Chan, Ka Po; Chung, Wai Kei Vicky; Hsu, Dany; Chan, Oi Man Iman; Chui, Ruby; Man, Ching Wah; Cheung, Ka Wai; Wong, Cherry; et al.
Abstract : Due to advances in medical care, a growing number of young people with life-limiting neurodevelopmental disabilities (LLNDDs) are now surviving into adulthood. However, the traditional model of care between pediatrics and adult medicine was fragmented and did not match their multi-facet needs. A special working group that includes pediatricians, adult palliative care team, and representatives from non-governmental organizations (NGOs) was formed, providing a period of joint care of 12–24 months before transitioning to the adult palliative care team. A retrospective case series of 19 young adults with LLNDDs, recorded during the July 2015–June 2020 period at the study institution is presented. Recruited patients' age ranged from 18 to 38 (mean 26.2 [ SD 6.1]). Majority of them ( n = 14) require residential care at long-term care facilities (LTCFs) and high level of nursing care, which include artificial nutrition ( n = 8) and home ventilator ( n = 5). All patients referred to our palliative care (PC) program were engaged in a structured advance care planning (ACP) process. Seventeen patients (89.5%) had their Do-Not-Resuscitate (DNR) directives in place and two mentally competent patients completed their own advance directive (AD). All deceased ( n = 10) had their DNR directives being honored. In conclusion, the palliative care needs of young adults suffering from LLNDDs should be properly addressed and implementation of a joint transitional care model between pediatrics and adult PC team is one possible method. Future research should encompass a better care model that addresses the multi-facet needs of young people suffering from LLNDDs, especially the transition from pediatrics to adult medicine.